2019
DOI: 10.1371/journal.pone.0211768
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to self-care recommendations and associated factors among adult heart failure patients. From the patients’ point of view

Abstract: BackgroundNowadays, heart failure (HF) related morbidity and mortality rate is increasing globally. Younger populations happen to be more affected by HF in sub- Saharan African than the western countries. Even though medications, low sodium diet, regular exercise, and weight monitoring are essential to control heart failure symptoms and its exacerbation, poor adherence to these self-care recommendations is contributing to an increased in hospitalization, morbidity, and mortality. Therefore, this study aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
109
5
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(134 citation statements)
references
References 50 publications
13
109
5
7
Order By: Relevance
“…Although this systematic review did not allow us to clearly conclude what duration was the best or most adequate, the analysis revealed that the most-effective interventions were those of the shortest duration, and especially those that had a follow-up period. This may have to do with the fact that compliance with both pharmacological and non-pharmacological therapies is generally low in chronic disease patients [5153] and it even decreases over time [54,55], since, in short-term interventions, both patients and staff are more engaged in the process.…”
Section: Discussionmentioning
confidence: 99%
“…Although this systematic review did not allow us to clearly conclude what duration was the best or most adequate, the analysis revealed that the most-effective interventions were those of the shortest duration, and especially those that had a follow-up period. This may have to do with the fact that compliance with both pharmacological and non-pharmacological therapies is generally low in chronic disease patients [5153] and it even decreases over time [54,55], since, in short-term interventions, both patients and staff are more engaged in the process.…”
Section: Discussionmentioning
confidence: 99%
“…Gender was not an independent predictor of compliance in multiple regression analysis and had no significance fo with treatment in cardiovascular disease is still ongoing [28][29][30]. There are few publications that discuss the impact of gender on compliance in HF, but those that do show a positive impact for male patients [3,[31][32][33]. The question remains as…”
Section: Plos Onementioning
confidence: 99%
“…3 Despite the evidence supporting the benefits of HF selfcare, 4 patients find it difficult to perform self-care, and self-care is often insufficient. [5][6][7] Investigators are struggling to find interventions that can effectively improve self-care. Recent trials of various interventions have had inconsistent results.…”
Section: Introductionmentioning
confidence: 99%